Linguistic but Not Cognitive Weaknesses in Deaf or Hard-of-Hearing Poor Comprehenders. (7th April 2021) - Deng, Qinli; Tong, Shelley Xiuli
Abstract: This study examined the reading comprehension profiles, and the related linguistic and cognitive skills, of 146 Chinese students in Grades 3–9 who are deaf or hard of hearing (d/Dhh). Employing a rigorous regression approach, the current study identified 19 unexpected poor comprehenders, 24 expected average comprehenders, and 16 unexpected good comprehenders. Compared to the expected average and unexpected good comprehenders, the unexpected poor comprehenders performed worse in broad linguistic skills (i.e., Chinese sign language comprehension, vocabulary, and segmental and suprasegmental phonological awareness), but their weaknesses in cognitive skills (i.e., working memory and executive function) were less severe. These findings suggest that weak linguistic skills are possible indicators of reading comprehension difficulties for students who are d/Dhh.